an Analysis of Students Difficulties in Translating Poetry from Indonesian to English at the Second Grade of SMA Swasta HKBP Sidorame Medan - Sembiring, Tasya Amelia; Tampublon, Sahlan; Pakpahan, Carolina (LPPPI Publishing, 2025)
This study focuses on knowing what kinds of difficulties were faced by second grade students of SMA Swasta HKBP Sidorame Medan while translating a poetry from Indonesian to English. This research used descriptive qualitative method used theory from Eggins (2004). The population of this research was second grade students of SMA HKBP Sidorame and the sample were 10 students from second grade.The source of data were 10 work sheets of students translation result. Meanwhile, the data of this research were the sentences that contain a mistake or error in meaning after being translated to English language . The result of the study showed that students' struggles translating poetry from Indonesian to English due to a lack of vocabulary. Students perform poorly while translating, particularly when it comes to stylistic translation.